Human Capital and Entrepreneurship Research: A Critical Review and Future Directions. (May 2016) - Marvel, Matthew R.; Davis, Justin L.; Sproul, Curtis R.
Human capital has emerged as a highly utilized theoretical lens through which scholars can better understand entrepreneurship. To synthesize the progress of this stream and promote its use, we review 109 articles in leading management and entrepreneurship journals over two decades. We organize our discussion in terms of multi–theory approaches, methods and analyses, constructs, and study focus. A number of research gaps and promising areas for inquiry are put forward. We develop a typology of human capital and discuss how future investigations of types of human capital related to the entrepreneurship process can benefit research and practice.